SIKAP MASYARAKAT TERHADAP PERBURUAN DAN PERDAGANGAN ORANGUTAN (Pongo pygmaeus) DI DESA KEPARI KECAMATAN SUNGAI LAUR KABUPATEN KETAPANG - Islami, Rinta; Fahrizal, .; AM, Iskandar (JURNAL HUTAN LESTARI, 2017)
Borneo orangutan (Pongo pygmaeus) was the only great apes that lives in Asia, one of in Indonesia. The Kepari village was one of distribution of orangutans in West Borneo, but the number of wild populations always decreased, based on the red list issued by IUCN in 2015, orangutan defined as animals that have endangered status, in addition to the orangutan was also listed in Appendix I CITES which means both animals and all products derived therefrom should not be traded anywhere. Success or failure of conservation undertaken by the government can’t be separated from the attitude of the community. This study aims to determine how public attitudes toward hunting and trade of orangutans and analyze the relationship between attitudes towards hunting and trade of orangutans with the level of perception, knowledge, and cosmopolitan. The results showed that people tend neutral attitude towards hunting and trade of orangutans, and the results of the analysis showed that the level of perception, knowledge, and cosmopolitan associated with public attitudes toward hunting and trade of orangutans. Keywords: Borneo orangutan, Hunting and Trade, Public Attitudes.